A Polymer Canvas with the Stiffness of the Bone Matrix to Study and Control Mesenchymal Stem Cell Response. Issue 10 (13th January 2023) - Zanut, Alessandra; Li, Rui; Deng, Ru; Liu, Xiangyu; Rejhon, Martin; Chen, Weiqiang; Weck, Marcus; de Peppo, Giuseppe Maria; Riedo, Elisa
Abstract: Reproducing in vitro the complex multiscale physical features of human tissues creates novel biomedical opportunities and fundamental understanding of cell−environment interfaces and interactions. While stiffness has been recognized as a key driver of cell behavior, systematic studies on the role of stiffness have been limited to values in the KPa−MPa range, significantly below the stiffness of bone. Here, a platform enabling the tuning of the stiffness of a biocompatible polymeric interface up to values characteristic of human bone is reported, which are in the GPa range, by using extremely thin polymer films on glass and cross‐linking the films using ultraviolet (UV) light irradiation. It is shown that a higher stiffness is related to better adhesion, proliferation, and osteogenic differentiation, and that it is possible to switch on/off cell attachment and growth by solely tuning the stiffness of the interface, without any surface chemistry or topography modification. Since the stiffness is tuned directly by UV irradiation, this platform is ideal for rapid and simple fabrication of stiffness patterns and gradients, thus representing an innovative tool for combinatorial studies of the synergistic effect of tissue environmental cues on cell behavior, and creates new opportunities for next‐generation biosensors, single‐cell patterning, and lab‐on‐a‐chip devices. Abstract : A novel platform to tune the stiffness of a biocompatible polymeric interface up to values characteristic of the bone tissue (GPa range) using ultraviolet (UV) cross‐linking is reported. Since cell growth and differentiation are here controlled solely by the UV‐tunable stiffness of the polymer, this platform is ideal for the simple and rapid fabrication of stiffness patterns and gradients for various biomedical applications.